2008
DOI: 10.1371/journal.pone.0003113
|View full text |Cite
|
Sign up to set email alerts
|

Low Frequency Groans Indicate Larger and More Dominant Fallow Deer (Dama dama) Males

Abstract: BackgroundModels of honest advertisement predict that sexually selected calls should signal male quality. In most vertebrates, high quality males have larger body sizes that determine higher social status and in turn higher reproductive success. Previous research has emphasised the importance of vocal tract resonances or formant frequencies of calls as cues to body size in mammals. However, the role of the acoustic features of vocalisations as cues to other quality-related phenotypic characteristics of callers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
126
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(135 citation statements)
references
References 67 publications
9
126
0
Order By: Relevance
“…This result is probably associated with the wild reminiscent and evolutionary reproductive function (WILSON & EVANS, 2008;GEBERZAHN et al, 2009;RANDALL et al, 2009). Similar results were reported in the literature with respect to identifying birds' sex by the analysis of their vocalization acoustic parameters (VOLODIN et al, 2009), as well as the study of vocalization of other animal species (VANNONI & MCELLIGOTT, 2008) including primates (FISCHER et al 2004). Determining the threshold of male and female vocalization with accuracy requires the help of information technology tools.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…This result is probably associated with the wild reminiscent and evolutionary reproductive function (WILSON & EVANS, 2008;GEBERZAHN et al, 2009;RANDALL et al, 2009). Similar results were reported in the literature with respect to identifying birds' sex by the analysis of their vocalization acoustic parameters (VOLODIN et al, 2009), as well as the study of vocalization of other animal species (VANNONI & MCELLIGOTT, 2008) including primates (FISCHER et al 2004). Determining the threshold of male and female vocalization with accuracy requires the help of information technology tools.…”
Section: Resultssupporting
confidence: 85%
“…It might identify unusual traits related to animals' status (MANTEUFFEL & SCHÖN, 2004;CORDEIRO et al, 2009;GRANDIN, 2010;CHAN et al, 2011). Other studies show vocal signals as a prominent tool to identify the animals' sex (FISCHER et al, 2004;VOLODIN et al, 2005;VANNONI & MCELLIGOTT, 2008). Broiler sexing is a time-consuming task.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent theoretical and technical advances in mammalian bioacoustics, centred around the application of the source-filter theory of voice production to voiced signals (Fant 1960;Fitch 2002), have enabled investigators to understand the acoustic structure of mammal vocal signals according to their modes of production, and to predict the covariation of specific acoustic features with physiological or morphological attributes of callers (Fitch 1997;Riede & Fitch 1999;Reby & McComb 2003a;Harris et al 2006;Sanvito et al 2007;Vannoni & McElligott 2008;Charlton et al 2009). The source filter theory states that vocal signals result from a two-stage production process, with the glottal wave generated in the larynx (the source), being subsequently filtered in the supra-laryngeal vocal tract (the filter ;Fant 1960;Titze 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Several recent publications applying the source-filter framework to the study of mammal signals have shown that vocal tract resonances, which reflect the length and shape of the vocal tract, are reliable acoustic cues to body size (Fitch 1997;Riede & Fitch 1999;Reby & McComb 2003a;Harris et al 2006;Sanvito et al 2007;Vannoni & McElligott 2008;Charlton et al 2009) and identity (Rendall 2003;Kidjo et al 2008). By contrast, despite its dependence on the length, mass and tension of vocal folds (Titze 1994), in mammals the fundamental frequency of vocalizations does not consistently provide reliable information on body size (Lass & Brown 1978;Reby & McComb 2003a;Rendall et al 2005; but see Pfefferle & Fisher 2006).…”
Section: Introductionmentioning
confidence: 99%